Modeling and removal of back-scattered noise from rough topography in land seismic data - Montes, Luis; Vargas, Carlos; Pérez, Gabriel (CT&F - Ciencia, Tecnología y Futuro, 2005)
The seismic records of Colombian foothills are usually noisy and contaminated by coherent and high amplitude back-scattered associated with roughness topography, which obscure reflectors from deeper layers. To remove this back-scattered noise, filters have been applied getting satisfactory results for smooth topography and short offsets, but in general conventional methods yield unsatisfactory results. We applied an approach based in prediction and subtraction of the unwanted noise to attenuate it. The extracted source signature of each record and the shallow velocity model were input to the finite element software to model the acoustic wave equation, obtaining the back-scattered noise in each record. Each output was subtracted from its corresponding record, attenuating noticeably the noise. The procedure was applied in the shots records of a foothill seismic line providing an improved image of the stacked section after time processing. The software had been previously tested on synthetic data giving promising results.